(untitled) - Silverman, David I. (New York, 2002)
ACCESS THE FUTURE OF TRADING WITH Direct Access Futures Direct access-the phenomenon that transformed stock trading-is radically changing the futures industry as well. Professionals and individual investors alike need to understand these changes or face being left behind. Let futures expert David Silverman show you how to survive and profit in the uncharted waters of trading futures via direct electronic access-with Direct Access Futures. This comprehensive guide is filled with the latest tips, techniques, and technologies related to trading futures online and shows you how to take advantage of this giant leap in futures trading. Direct Access Futures provides you with: Varying types of direct access An inside look at how futures markets work, who uses them, and why Case studies, including the Chicago Mercantile Exchange's GLOBEX(r)2 An overview of major exchanges Trading products, including the e-mini S&P 500 and Nasdaq 100 contracts, currency futures contracts, and long-term interest rate futures Whether you make a living trading futures or just live for trading futures, Direct Access Futures should be your all-purpose guide to this versatile investment vehicle. Learn how to trade futures using direct access and watch your profits soar.
Keywords: Electronic trading of securities,Futures,Giao dịch chứng khoán điện tử,Tương lai